Shurlock shoe bag / Luqman Hakim Muhaiyuddin ... [et al.] - Muhaiyuddin, Luqman Hakim; Abu Bakar, Nurul Atiqah; Juharudin, Muhamamd Naqib; Ah Siak @ Mohd Helmi, Nurul Fatin Hamizah; Mohd Farid, Muhammad Faiq Irfan; Mohd Firdaus How, Syahirul Nidham How
One of the objectives of our product is to apply more safety profile towards a normal shoe bag. By using shoe bag as our benchmark, the normal shoe bag looks simple and efficient. We just have the idea to help people with various kind of problems regarding their shoes. Based on our survey, many people faced the trouble of missing their shoes in crowded places. This is burdensome to sportsmen and office worker that uses expensive shoes. Next, we find problems that many people face which is they need place to dry their shoe. Many sportsmen do not have the place to dry their shoe because some of them lived in a small house and small area. Drying in the house cause the house smelly and drying outside their house increase the chances of the shoe being stolen. But with a present of dehumidifier, they can dry their shoe in the bag. More safety and does not use huge spaces in your house. Other than that, our improved shoe bag can also solve the problem of need to dry their shoe on the go. This problem always occurs among sportsmen which when after finish training or any activities, they do not have the time to dry their shoes. Instead, they just put in the shoe bag which is not exposed and low ventilation for the shoe to dry, sometimes when they arrive home, they are too tired to dry their shoe and just let it be in the bag. This effects to damp and smelly shoe and they will be very uncomfortable to wear for the next occasion. As the shoe bag is packed with humidifier, they can dry their shoe in the bag. They can dry their shoe as long as it is put in the bag